Climate-smart agricultural practices, productivity, and food-nutrition security in rural South Africa: A dataset of smallholder maize farmers - Abeeb Babatunde Omotoso; Simon Sebatana Letsoalo; Saidat Adebola Daud; Christopher Tshwene; Abiodun Olusola Omotayo (Data in Brief, 2024)
The intensifying impacts of climate change have adversely affected smallholder maize farmers, leading to low productivity, decreased incomes, and food-nutrition insecurity. As a result, an understanding of farmers' adaptation techniques to offset the negative impacts of climate change is imperative. Here we present the data on the impact of climate-smart agricultural (CSA) practices on productivity and food-nutrition security (FNS) in the 2022-2023 agricultural production season among smallholder maize farmers in North-West Province, South Africa. The survey that gave this dataset was conducted via a multistage sampling technique through a well-structured questionnaire from 316 smallholder maize farmers selected from 20 randomly sampled villages in South Africa. The finding revealed that climate change is evident in the study location by the significant decline in productivity and FNS of the smallholder maize farmers. Notably, the productivity of CSA adopters and non-adopters is 13.85 and 7.26, respectively. We estimated the HFIAS of CSA adopters and non-adopters to be 2.23 and 5.85, respectively. Consequently, various CSAs adopted in the study area include drought-tolerant maize varieties (DTMV), mulching, cover cropping, and zero tillage. The study outcomes indicate that to achieve the FAO's sustainable agricultural goals and create a world free of hunger by 2030, South Africa's farmers must foster their CSA adoption intensity in order to enhance productivity and FNS through building resilience to climate change.